(96 - 3x4-5x8) +f-9 x 7 = 13 !
(23-6x3 + g) + 3 x 9 - 8 x 3 – 28 = 34
(3 x 9 + 7 xh-53) + 5 x2 - (12 - 4x 2) = 6 x 6
8 x 8-32 - (6xi - 51)-( 40 – 2 x 10 ) = 3 x 3
mai
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
(96-3x4-5x8)+f-9x7=13
(96-12-40)+f-9x7=13
(96-12-40)+f-63=13
44+f-63=13
-19+f=13
f=13+19
f=32
herealentagmailcom:
ok mă ajutați și cu următoarele?
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Biologie,
8 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă